Reliability and Diagnostic Accuracy of Radiography for the Diagnosis of Calcium Pyrophosphate Deposition: Performance of the Novel Definitions Developed by an International Multidisciplinary Working Group. Issue 4 (19th January 2023) - Sirotti, Silvia; Becce, Fabio; Sconfienza, Luca M.; Terslev, Lene; Naredo, Esperanza; Zufferey, Pascal; Pineda, Carlos; Gutierrez, Marwin; Adinolfi, Antonella; Serban, Teodora; MacCarter, Daryl; Mouterde, Gael; et al.
Abstract : Objective: To assess the reliability and diagnostic accuracy of new radiographic imaging definitions developed by an international multidisciplinary working group for identification of calcium pyrophosphate deposition (CPPD). Methods: Patients with knee osteoarthritis scheduled for knee replacement were enrolled. Two radiologists and 2 rheumatologists twice assessed radiographic images for presence or absence of CPPD in menisci, hyaline cartilage, tendons, joint capsule, or synovial membrane, using the new definitions. In case of disagreement, a consensus decision was made and considered for the assessment of diagnostic performance. Histologic examination of postsurgical specimens under compensated polarized light microscopy was the reference standard. Prevalence‐adjusted bias‐adjusted kappa values were used to assess reliability, and diagnostic performance statistics were calculated. Results: Sixty‐seven patients were enrolled for the reliability study. The interobserver reliability was substantial in most of the assessed structures when considering all 4 readers (κ range 0.59–0.90), substantial to almost perfect among radiologists (κ range 0.70–0.91), and moderate to almost perfect among rheumatologists (κ range 0.46–0.88). The intraobserver reliability was substantial to almost perfect for all the observers (κ range 0.70–1). Fifty‐one patients were included in the accuracy study. Radiography demonstrated an overall specificity of 92% for CPPD, but sensitivity remained low for all sites and for the overall diagnosis (54%). Conclusion: The new radiographic definitions of CPPD are highly specific against the gold standard of histologic diagnosis. When the described radiographic findings are present, these definitions allow for a definitive diagnosis of CPPD, rather than other calcium‐containing crystal depositions; however, a negative radiographic finding does not exclude the diagnosis.